The Implementation of 5C Principle and Maqashid Al-Sharia at Baitul Māl wat Tamwil BMT DAQU Bojonegoro, Indonesia - Dewi Gita Ramadhanti; Ifa Khoiria Ningrum; Muhammad Zaenal Abidin (Prodi Hukum Ekonomi Syariah, Fakultas Syariah, IAIN Palopo, 2026)
Purpose - This study aims to analyze the application of the 5C prudential principle consisting of Character, Capacity, Capital, Collateral, and Condition in financing practices at BMT DAQU Klepek Sukosewu Bojonegoro, Indonesia. The study also examines the relationship between the implementation of the 5C principle and the values of Sharia Economic Law through the perspective of Maqasid al Sharia, particularly in the context of the increasing level of Non-Performing Financing (NPF). Method – This research applies a qualitative approach with a field research design. Data were collected through semi structured interviews with Sharia administrators and supervisors, direct observation of financing practices, and documentation related to the financing process and the management of problematic financing. Data analysis was conducted using the interactive model of Miles and Huberman which consists of data reduction, data display, and conclusion drawing. Data validity was ensured through source triangulation and method triangulation. Results – The findings show that weaknesses in several elements of the 5C assessment contribute to the increase of problematic financing. Limitations in evaluating character, capacity, and economic conditions of customers affect the quality of financing decisions. The study also finds that the settlement of problematic financing at BMT DAQU is conducted through approaches which consider both managerial prudence and Sharia based ethical considerations. Implications – This study contributes to strengthening risk management in Islamic microfinance institutions. The integration of the 5C prudential principle with the values of Maqasid al-Sharia, particularly the principles of hifz al-mal and justice, can support more responsible financing practices and improve the governance of Islamic microfinance institutions.